THE EFFECT OF TEAMS GAMES TOURNAMENT (TGT) MODEL ASSISTED BY QUESTION CARDS ON STUDENTS' COGNITIVE PHYSICS LEARNING OUTCOMES: PENGARUH MODEL TEAMS GAMES TOURNAMENT (TGT) BERBANTUAN QUESTION CARD TERHADAP HASIL BELAJAR KOGNITIF FISIKA SISWA - Siti Rohmaniah; I Made Astra; Hadi Nasbey (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2025)
The aim of this research is to identify the differences and effects of using the Teams Games Tournament (TGT) model assisted by Question Cards on students' cognitive learning outcomes. The method used in this research is a quasi-experimental method. Before conducting the hypothesis test, prerequisite data tests were carried out, including normality testing and homogeneity testing. The hypothesis testing uses the t-test. The results of this study are expected to show significant differences and effects after the treatment of using the Teams Games Tournament (TGT) learning model assisted by Question Cards, which can be analyzed through hypothesis testing with the t-two sample assuming equal variances where the value of tcalculated > ttable, and in the independent samples t-test, the significance value of the t-test must be < 0.05.